Chronic venous insufficiency in pregnant women - Nabnita Patnaik; Nihar Ranjan Pradhan (Indian Journal of Vascular and Endovascular Surgery, 2021)
Objective: C-hronic venous insufficiency (CVI) occurs in up to 80% of pregnant women, while around seven of every 1000 pregnant mothers face venous thromboembolism and pulmonary embolism. A review of the literature on CVI in pregnant women reveals considerable guidance for their treatment. Pregnancy causes significant hemodynamic changes within the circulatory system. Pregnancy has significant effects on the lower extremity venous system. Increasing venous pressure and blood volume, in combination with reduced flow rates within the deep veins, predisposes pregnant women to both primary and secondary CVI. This article highlights the specific physiologic and hemodynamic changes that occur during pregnancy and examines the nonpharmacologic, pharmacologic, and invasive interventions that are appropriate for both prophylaxis and treatment of CVI. Methods: This study is a review article of the key literature related to CVI in pregnancy. Results: Consequences of pregnancy can result in venous disease only during pregnancy or, particularly in the multiparous patient, can progress to CVI. Significant hemodynamic changes occur in the lower extremities during pregnancy. Conclusions: There is a paucity of data available to construct guidelines for care, particularly in pregnant patients with symptomatic superficial venous insufficiency. The physiologic changes throughout the arterial and venous systems during pregnancy are well documented.